2020
DOI: 10.1186/s12967-020-02462-1
|View full text |Cite
|
Sign up to set email alerts
|

32A9, a novel human antibody for designing an immunotoxin and CAR-T cells against glypican-3 in hepatocellular carcinoma

Abstract: Background: Treatment of hepatocellular carcinoma (HCC) using antibody-based targeted therapies, such as antibody conjugates and chimeric antigen receptor T (CAR-T) cell therapy, shows potent antitumor efficacy. Glypican-3 (GPC3) is an emerging HCC therapeutic target; therefore, antibodies against GPC3 would be useful tools for developing immunotherapies for HCC. Methods: We isolated a novel human monoclonal antibody, 32A9, by phage display technology. We determined specificity, affinity, epitope and anti-tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…The use of Glypican-3 (GPC3) antibody in combination with CAR T therapy can be a useful method in the treatment of liver malignancies. Liu and coworkers showed that the use of 32A9 monoclonal antibody /CAR T cells kill (GPC3 + ) HCC cells in vitro and regresses liver xenograft tumor in vivo [100]. Another study illustrated that GPC3/CAR T cells expressing IL15/21 promoted the antitumor responses of T cells against HCC [101].…”
Section: Liver Cancermentioning
confidence: 99%
“…The use of Glypican-3 (GPC3) antibody in combination with CAR T therapy can be a useful method in the treatment of liver malignancies. Liu and coworkers showed that the use of 32A9 monoclonal antibody /CAR T cells kill (GPC3 + ) HCC cells in vitro and regresses liver xenograft tumor in vivo [100]. Another study illustrated that GPC3/CAR T cells expressing IL15/21 promoted the antitumor responses of T cells against HCC [101].…”
Section: Liver Cancermentioning
confidence: 99%
“…Antibodies and recombinant proteins YP7 and 32A9 are GPC3-specific monoclonal antibodies generated in our previous studies. [30][31][32] YP7 is a mouse antibody and was humanized (named hYP7) for the generation of CAR-T cells. The recombinant sGPC3 (Q25-S550) protein with a hexa-histidine tag at the C-terminal end, or with a wild-type human Fc (hFc) tag or mutant hFc tag containing three mutations (N297A/ L234A/L235A) reported to abolish unexpected binding to the Fcγ receptor 33 34 were cloned into the pFUSE vector (InvivoGen, San Diego, California, USA).…”
Section: Clinical Samples and Cellsmentioning
confidence: 99%
“…Antibody-targeting of SDC1 has been used alone or combined with chemotherapy to treat multiple myeloma [231], and a clinical trial using CAR-T cells recognising SDC1 suggests that the treatment is safe, well-tolerable and has potential antitumour activity [232]. In the same line, in hepatocellular carcinoma, the strategies of immunotoxin and CAR-T cells against GPC3 are showing promising results and are under clinical trials [233][234][235].…”
Section: Heparan Sulfate-based Therapeutic Opportunitiesmentioning
confidence: 99%